Relevance of Teledentistry: Brief Report and Future Perspectives - Carlo Fornaini; Jean-Paul Rocca (Tehran University of Medical Sciences, 2022)
Teledentistry is a type of telemedicine and telehealth that aims to make all major specialties of the discipline easier through a remote approach to prevention and treatment of oral and dental issues. This new method enables distant access to individuals instead of direct, face-to-face, doctor-patient contact and has been made possible thanks to developments in information technology. Teledentistry was described in 1997 as "... the practice of using video-conferencing technologies to diagnose and provide advice about treatment over a distance", and today it represents a modern way to practice dentistry by integrating digital imaging, electronics, health records, and telecommunications technology via an internet connection. This approach facilitates patients' access to care in remote settings and also enables specialists at distant locations to arrive at a correct diagnosis as well as to propose proper therapy or refer patients, where warranted. The current brief report aims to describe the present and future of this modern approach in dentistry and its advantages in patient management from prevention to diagnosis to treatment.